2020
DOI: 10.1038/s41419-020-03121-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-488 inhibits proliferation and motility of tumor cells via downregulating FSCN1, modulated by Notch3 in breast carcinomas

Abstract: As important modulators in multiple physiological processes, microRNAs (miRNAs) have been reported in various malignant tumors, including breast cancer. The current study investigated the function of a new tumor suppressor microRNA, miR-488, and its molecular mechanism of metastasis in breast cancers. CCK8 and transwell assays revealed that the upregulated miR-488 level significantly inhibited the proliferation and migration of breast cancer cells. As a potential downstream gene, the mRNA and protein level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…To elucidate the role of Fascin in TNBC, we performed loss-of-function assays in HS578T and MDAMB231 cell lines. As expected, the wound-healing, transwell migration, and matrigel invasion assays confirmed that the knockdown of Fascin significantly suppressed TNBC cells migration and invasion, which was consistent with the findings of previous studies [18,26] (Fig. 1F, G).…”
Section: Fascin Is Highly Expressed In Tnbc and Enhances Cells Metast...supporting
confidence: 92%
See 1 more Smart Citation
“…To elucidate the role of Fascin in TNBC, we performed loss-of-function assays in HS578T and MDAMB231 cell lines. As expected, the wound-healing, transwell migration, and matrigel invasion assays confirmed that the knockdown of Fascin significantly suppressed TNBC cells migration and invasion, which was consistent with the findings of previous studies [18,26] (Fig. 1F, G).…”
Section: Fascin Is Highly Expressed In Tnbc and Enhances Cells Metast...supporting
confidence: 92%
“…Mechanistically, we observed that Fascin can downregulate xCT at the posttranscriptional level in TNBC. The results of previous studies indicated that Fascin is a downstream effector protein that is regulated by a number of other factors, such as transcription factors [34,35], microRNAs [26,36], and long-noncoding RNAs [15,37]. However, accumulating evidence has demonstrated that Fascin can also regulate other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a 200 μL yellow pipette tip was used to scratch a gap on the cellular monolayers, and cells were then washed with phosphate buffer (PBS) to remove the suspended cells, followed by the incubation in serum-free DMEM medium for additional 24 h. Images were captured using an optical microscope and the gap sized was recorded. To determine the invasive capacity of osteosarcoma cells, transwell experiment was performed as previously described [42][43][44].…”
Section: Cellmentioning
confidence: 99%
“…Plasmids carrying the human miR-128-3p mimic (miR-128-3p mimic) or miRNA negative control mimic (NC), a lentiviral vector containing the human miR-128-3p inhibitor (LV-miR-128-3p-inhibitor), and the corresponding control (LV-NC) were purchased from GenePharma (Shanghai, China). HGC-27 cells were transfected using Lipofectamine 3000 (Thermo Fisher Scientific, Waltham, MA, USA), and GES-1 cells were infected with LV-miR-128-3p-inhibitor or LV-NC [ 17 , 18 ]. At 48 h posttransfection or 72 h after lentivirus infection, according to the manufacturer’s instructions, the culture media were collected, filtered, and stored in a refrigerator at 4°C.…”
Section: Methodsmentioning
confidence: 99%